ANALISIS MENDALAM TENTANG KEBERHASILAN MODEL TEAMS GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA - Afa Wibowo (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This research examines the effectiveness of the Team Game Tournament (TGT) learning model in increasing student motivation and academic achievement. TGT is a collaborative learning model that involves forming small, heterogeneous groups (4-6 students) for collaborative learning at the stages of presenting material, group formation, games, competitions and prizes. Analysis of 25 research papers proves that the application of the TGT model is effective in increasing student motivation and learning outcomes significantly. Research found that student learning motivation increased by 25% and student learning outcomes increased by 14.18% after implementing TGT. Additionally, TGT increases student activity, engagement, social skills, understanding of material, and overall performance. This research concludes that the TGT model is effective in creating an interactive, collaborative, and enjoyable learning environment as well as increasing motivation, learning outcomes, and overall student development.